Strategic importance of the coal industry in the industrial policy of the state - Karenov , R.S. (BUKETOV BUSINESS REVIEW, 2018)
It is underlined that Kazakhstan occupies a high place in the world both in terms of proved coal reserves and in terms of production volume. It is concluded that the development of the industry in recent years has been associated primarily with negative external factors. It is proved that, first of all, the decline in commodity prices, the reduction of export earnings in the economy, weak domestic demand, the weakening of economic activity, the reduction of electricity production, a general decline in Russia and a deliberate reduction in the use of Kazakh coal by Russian thermal power stations. It is noted that coal is the most important energy carrier on the planet and the refusal to produce it in the short term is not acceptable. It is substantiated that in Kazakhstan in the future special attention should be paid to projects that can open new sustainable prospects for the coal mining industry. It is argued that in the future, an increase in the redistribution of coal products, as well as prospects for the development of coal chemistry, may be among the measures that will help preserve personnel and the coal industry itself, which is leading in the economy of the republic. It is alleged that recently, in the context of the rapid growth in prices for hydrocarbon fuels and the development of technologies for processing and burning coal that have increased the efficiency of its use for generating electricity and have reduced the negative environmental impact of this process, there has been an increase in the attractiveness of coal not only for developing but also for developed countries of the world.